Упростите выражение [latex] \frac{61}{16+ 4\sqrt[3]{3}+ \sqrt[3]{9} } + \sqrt[3]{3} [/latex]
Упростите выражение
[latex] \frac{61}{16+ 4\sqrt[3]{3}+ \sqrt[3]{9} } + \sqrt[3]{3} [/latex]
Ответ(ы) на вопрос:
[latex] \frac{61}{16+4 \sqrt[3]{3}+ \sqrt[3]{9} }+ \sqrt[3]{3}= \frac{61+ \sqrt[3]{3}*(16+4 \sqrt[3]{3}+ \sqrt[3]{9}) }{16+4 \sqrt[3]{3}+ \sqrt[3]{9} }= \frac{61+16 \sqrt[3]{3}+4 \sqrt[3]{9}+ \sqrt[3]{27} }{16+4 \sqrt[3]{3}+ \sqrt[3]{9} }= [/latex][latex]= \frac{61+16 \sqrt[3]{3}+4 \sqrt[3]{9}+3 }{16+4 \sqrt[3]{3}+ \sqrt[3]{9} }= \frac{64+16 \sqrt[3]{3}+4 \sqrt[3]{9} }{16+4 \sqrt[3]{3}+ \sqrt[3]{9} }= \frac{4*(16+4 \sqrt[3]{3}+ \sqrt[3]{9}) }{16+4 \sqrt[3]{3}+ \sqrt[3]{9} }=4 [/latex]
Ответ: 4
Не нашли ответ?
Похожие вопросы